Holding Up a Democratic Facade: How ‘New Work Organizations’ Avoid Resistance and Litigation When Dismissing Their Managers - Degen, Johanna L.; Zekavat, Massih (Frontiers in Psychology, 2022)
New work is used as a general term to summarize professional developments in contemporary work style, structure and modus of organizations and society— on individual levels, this includes e.g. collaborative working, flexible working hours, and on organizational levels, e.g. featuring flat hierarchies, participatory decision-making. Contemporary corporations strive to orient toward the concept of new work to keep up with stakeholder demands, for instance in their branding strategies as an employer. However, studies on organizational practices indicate that alongside explicit values and agendas, organizations tend to slyly exert power to secure their (economic) interests. Constructive dismissal is one such instance where contractually protected employees are made to resign their positions because the work environment is altered to become increasingly unbearable. This research analyzes two case studies to explicate routine dismissal procedures at the managerial level in two internationally operating German corporations. Both corporations explicitly profile as new work environments and are structured according to democratic principles including flat hierarchies, feature institutionalized diversity management including control committees for equal opportunities, and emphasize values such as workplace dignity, employee agency and equality. The data contains long-term participatory observation collected over a 6-month period from two managers of 5 and 8 years of experience in managerial duties. The content analysis of data reveals characteristics of everyday processes in these organizations, especially in terminating managers. The findings are presented as the ‘model of the silent dismissal’, containing seven types of managerial termination carried out by implicit power and symbolic conventions that circumvent subject participation and litigation effortlessly. After exposing the model’s mechanisms, we turn to discuss its meaning for both terminated and surviving subjects against a critical theoretical framework of neoliberalism, democracy, and power.